When the Senate Worked for Us : The Invisible Role of Staffers in Countering Corporate Lobbies - Pertschuk, Michael, 1933- (Book collections on Project MUSE., 2017)
Inside stories of maneuvering by activist staffers fighting to enact laws in the public interest.